From literary trope to hermeneutic mechanism. Metaphor: transformation and change of linguistic stage (2010)
This paper proposes metaphors as the re-descriptive renewal mechanism of language. It starts with a critique to its use as a mere literary figure, then, it develops its semantic influence that turns it into the strength that allows the hermeneutic openness between the works of literary art and their readers, due to a special relationship that links them. Such a linking allows the modification of the text tissue that the readers have and gives life to the works when widening their hermeneutic horizon. From this point of veiw, metaphors give the possibility of achieving an original style for identity as it proposes an original reading of the work. Metaphors change the perspective into language, from the strongest certainties of the sceintific region to the transient poetic moods.